2008
DOI: 10.1007/s11934-008-0041-0
|View full text |Cite
|
Sign up to set email alerts
|

Extended lymph node dissection for prostate cancer

Abstract: Lymph node status is an important determinant for the management of patients with newly diagnosed prostate cancer. Given the significant limitations of cross-sectional and functional preoperative imaging in the detection of small metastases, pelvic lymph node dissection remains the only reliable staging method in clinically localized prostate cancer. Although lymph node dissection is a well-established form of staging in prostate cancer, controversy remains about indications and the surgical extent of the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In these situations, often, urologists will dissect the obturator, external iliac, hypogastric (internal iliac) and common iliac nodes; however, additional nodes in presacral, paraaortic, pararectal and paravesical regions can be involved and dissected as illustrated in lymphoscintigraphic studies of the prostate. [8][9][10] These studies have confirmed the lymphatic drainage of the prostate to be unique and that different nodal groups can be affected independently of each other with authors reporting that up to 40% of lymph nodal involvement (LNI) can be missed with a limited node dissection alone. 11,12 This variability in the extended dissection template makes it difficult to compare results with documented average nodal yields for an ePLND ranging from 11.6 to 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these situations, often, urologists will dissect the obturator, external iliac, hypogastric (internal iliac) and common iliac nodes; however, additional nodes in presacral, paraaortic, pararectal and paravesical regions can be involved and dissected as illustrated in lymphoscintigraphic studies of the prostate. [8][9][10] These studies have confirmed the lymphatic drainage of the prostate to be unique and that different nodal groups can be affected independently of each other with authors reporting that up to 40% of lymph nodal involvement (LNI) can be missed with a limited node dissection alone. 11,12 This variability in the extended dissection template makes it difficult to compare results with documented average nodal yields for an ePLND ranging from 11.6 to 28.…”
Section: Discussionmentioning
confidence: 99%
“…While it is generally accepted that a limited nodal dissection removes the obturator package and the standard dissection additionally involves dissection of the external iliac nodes, there is no standardization or universally accepted operative template regarding the extended lymph node dissection. In these situations, often, urologists will dissect the obturator, external iliac, hypogastric (internal iliac) and common iliac nodes; however, additional nodes in presacral, paraaortic, pararectal and paravesical regions can be involved and dissected as illustrated in lymphoscintigraphic studies of the prostate . These studies have confirmed the lymphatic drainage of the prostate to be unique and that different nodal groups can be affected independently of each other with authors reporting that up to 40% of lymph nodal involvement (LNI) can be missed with a limited node dissection alone …”
Section: Discussionmentioning
confidence: 99%
“…Intraoperatively, the radioactive SNs can be detected with a gamma-ray detection probe. Both open and laparoscopic approaches have been extensively studied in prostate cancer although there is a shift toward the less invasive laparoscopic and robot-assisted techniques [ 48 , 62 , 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data from surgical series have shown that the combination of RP and extended PLNDs can improve biochemical‐free progression and potentially DSS [72,73]. There is also known to be a direct relationship between the number of LNs removed at surgery and PFS and CSS whether or not they harbour obvious metastatic disease [74,75]. In a recent study of 614 men by Schiavina et al .…”
Section: Role Of Ln Therapy In High‐risk Prostate Cancermentioning
confidence: 99%